The disabled contract : severe intellectual disability, justice and morality / Jonas-Sébastien Beaudry, McGill University. - Beaudry, Jonas-Sébastien, 1981- (Cambridge disability, law and policy series., 2021)
Social contract theories generally predicate the authority of rules that govern society on the idea that these rules are the product of a contractual agreement struck between members of society. These theories embody values, such as equality, reciprocity and rationality, that are highly prized within our culture. Yet a closer inspection reveals that these features exclude other important values, relations and even persons from the realm of contractual morality and justice, especially people with severe intellectual disabilities. Jonas-Sébastien Beaudry explores the moral status of intellectually disabled people in social contract thought and argues that this tradition needs to be revisited to include the most vulnerable. Addressing this problem will have concrete repercussions in law and policy, because many issues that people with disabilities face are connected to deeply rooted assumptions about their status as full citizens or full members of our moral, political and legal communities.